Utilization of waste coconut coir dust as a source of fuel - Festin, Teodorico F. (Philippine Engineering Journal)
The Philippines is considered one of the world's largest producers of coconuts with its yield of around 8.6 x 10 nuts annually. Oil from the meat is the major product desired but many other-by-products can be obtained. The husk, which is about 35% of the weight of the matured fruit, can be utilized for many purposes. It can be used as a fuel for drying copra, as a raw material for handicrafts and other minor applications, or for the production of coir fibres. In the extraction of the fibre however, large amounts of waste coir dust, to the extent of about 60% of the weight of the husk, are produced. The disposal of this waste coir dust poses some problems for the coir fibre extraction plants. It readily accumulates and occupies much space which are ideal breeding places for pests. The present method of disposal, landfill, is expensive and time consuming. Utilization, therefore rather than mere disposal would be of great benefit to the coconut industry. The Philippine's present output of coir fibre is only 1% of the world market because of the dust disposal problem. The recycling of the waste as a source of fuel or as a source of industrial chemicals will improve the profitability of the coir fibre processing industry. The research on the production of a gaseous fuel (coco gas) from coir dust was primarily aimed at solving the problem of water coir dust disposal.